STUDI KINERJA DEWAN PERWAKILAN RAKYAT DAERAH (DPRD) KABUPATEN PACITAN DALAM PELAKSANAAN FUNGSI LEGISLASI PERIODE 2019-2024 - Priska Susilowati; Priyastiwi Priyastiwi (Jurnal Riset Manajemen Akuntansi Indonesia, 2026)
This studyaims to analyze the performance of the Regional House of Representatives (DPRD) of Pacitan Regency for the 2019–2024 period in implementing its legislative function. As a legislative body, the DPRD serves as a partner of the regional government in formulating, discussing, and enacting regional policies through the establishment of local regulations. However, the legislative function of the DPRD of Pacitan Regency has not been fully optimal, as indicated by the limited number of regional regulations initiated by the DPRD itself. This research employed a descriptive qualitative approach with data collected through interviews, observations, and documentation studies involving DPRD leaders, members, and related stakeholders. The analysis was based on Levine’s (1990) theory, which measures organizational performance through three indicators: responsiveness, responsibility, and accountability. The findings reveal that the responsiveness aspect is relatively good, as the DPRD has followed up on community aspirations through several local regulations. However, the responsibility aspect remains less optimal due to delays and irregularities in the legislative process, while accountability has not functioned effectively since public interests have not yet become the main orientation. The study concludes that institutional capacity and transparency need to be strengthened to enhance the DPRD’s legislative performance in a more responsive, responsible, and accountable manner.